Up in the air - Clifford, Jeffrey; Dubiecki, Daniel; Reitman, Ivan.; Reitman, Jason, 1977-; Turner, Sheldon; Clooney, George; Farmiga, Vera.; Kendrick, Anna.; Bateman, Jason; Morton, Amy.; Lynskey, Melanie; Simmons, J. K.; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2010)
Ryan Bingham is a corporate downsizing expert. When Bingham goes on his last cross country firing expedition, he will learn that life isn't about the journey, but about the connections made along the way.
Based on the novel by Walter Kirn.
Special features: Filmmakers' commentary; featurette; deleted scenes; music video; trailers.
Director of photography, Eric Steelberg ; editor, Dana E. Glauberman ; music, Rolfe Kent.
George Clooney, Vera Farmiga, Anna Kendrick, Jason Bateman, Amy Morton, Melanie Lynskey, J. K. Simmons, Sam Elliott.
MPAA rating: R; for language and some sexual content.
DVD, region 1, widescreen ([1.85:1]) presentation; Dolby Digital 5.1.
Keywords: Downsizing of organizations -- United States -- Drama; Specialists -- United States -- Drama; Frequent flyer programs -- United States -- Drama; Man-woman relationships -- United States -- Drama; Severance pay -- United States -- Drama; Brothers and sisters -- United States -- Drama; Relaciones hombre-mujer -- Estados Unidos -- Teatro; Hermanos -- Estados Unidos -- Teatro; Romantic comedy films; Video recordings for the hearing impaired; Feature films